Clostridium perfringens enterotoxin and Clostridium difficile toxin A/B do not play a role in acute haemorrhagic diarrhoea syndrome in dogs. (7th March 2015) - Busch, K.; Suchodolski, J. S.; Kühner, K. A.; Minamoto, Y.; Steiner, J. M.; Mueller, R. S.; Hartmann, K.; Unterer, S.
Abstract : Although an association between clostridial pathogens and canine idiopathic acute haemorrhagic diarrhoea syndrome (AHDS) has been described, the relevance of those bacteria and their toxins remains unclear. The aim of this study was to evaluate the association between severity of clinical signs and presence of Clostridium perfringens enterotoxin (CPE) and Clostridium difficile toxin A/B (CDT A/B) in faeces of dogs with AHDS. Faecal samples of 54 dogs with idiopathic AHDS were tested by qualitative CPE and CDT A/B ELISA, and PCR was performed to detect enterotoxin genes of C. perfringens ( cpe ) and toxin B genes of C. difficile ( cdt b ). Prevalence of cdt b and CDT A/B in dogs with AHDS was 10/54 and 2/54 versus 3/23 and 0/23 in control dogs. Prevalence of cpe was 35/54 in affected versus 9/23 in control dogs. Prevalence of CPE in dogs with AHDS (13/54) was higher compared with control dogs (0/23). No significant difference was detected between CPE‐positive and ‐negative and between cpe ‐positive and ‐negative dogs in severity of clinical signs, duration of hospitalisation, mortality rate and selected laboratory parameters. This study suggests that CPE and CDT A/B do not play a role in idiopathic AHDS, are not associated with clinical parameters in affected dogs and cannot be used to predict disease outcome.